Evaluation of a home medicines review program at an Aboriginal Medical Service in the Northern Territory - Deidun, D.; Ali, Mohammed; Madden, A.; O'Brien, M. (2019)
© 2019 The Society of Hospital Pharmacists of Australia Background: The home medicines review (HMR) program aims to achieve quality use of medicines. In 2009, the model of HMR provision at Danila Dilba Health Service (DDHS) in Darwin was adjusted to include the services of a dedicated consultant pharmacist and an expanded role for an Aboriginal Health Worker (AHW) in the HMR process. Aim: This study evaluated a unique program providing HMRs to Indigenous clients of DDHS. Methods: A retrospective review of HMRs was conducted for clients at DDHS between December 2009 and December 2010 to determine relevant time frames between HMR activities, reasons for referral, issues identified by the pharmacist, education provided, recommendations and uptake of recommendations. Awareness and attitudes to the program among general practitioners (GPs), AHWs, and pharmacists were also evaluated using a self-administered questionnaire. Results: Sixty-four HMRs were conducted. Thirty-nine (61%) follow-up appointments were documented and 30 Medicare claims made. The average time between referral and follow-up was 66 days. For most HMRs, more than one reason for referral was identified. In all, 348 issues were identified, 256 educational activities undertaken and 379 recommendations made. Fifty-two per cent of recommendations were implemented. Attitudes to the HMR program were positive. Common themes included the importance of cultural safety, particularly the inclusion of an AHW in HMR activities and difficulties associated with the follow-up of patients. Conclusion: Uptake of recommendations for improvements in the quality of documentation, GP follow-up and the referral system will enhance the HMR service at DDHS.